(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Literature concept is considered, first of all, as a unity of individual mind of the field of concept verbally expressed in a single text of the writer’s work. It is noted that the nature and methods of expressing the national concept in the literature world of a certain author determine the characteristics of his individual concept. It was found that the use of a certain method of analysis of literature concepts largely depends on the studied object (a specific author, a specific literature text), as well as the type of the studied concept.